2021
DOI: 10.1038/s41598-020-79873-z
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between self-care behavior and disease knowledge on the decline in renal function in chronic kidney disease

Abstract: Multidisciplinary care can improve the outcomes of chronic kidney disease (CKD), however the contribution of self-care behavior and knowledge about CKD is unclear. This study enrolled 454 participants with CKD stages 1–5 not on dialysis. Structured questionnaires were used to evaluate self-care behavior and kidney disease knowledge. Rapid decline in renal function was defined as the decline in estimated filtration rate > 3 ml/min per 1.73 m2/year within 1-year prior to enrollment. The mean age of all study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 29 publications
3
20
0
5
Order By: Relevance
“…Studies have documented that knowledge is essential for slowing kidney function advancement through behavior adjustments, such as physical exercise, dietary changes, patient monitoring (eg, blood pressure [BP] and blood glucose), and adherence to medication [ 9 ]. Patients with CKD may benefit from knowledge to change their behavior, improve their outcomes, and lower their mortality rates [ 10 ]. Considering the increasing prevalence of CKD, only 6% of the general population and 10% of those at high risk are aware of their CKD status in LMIC [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have documented that knowledge is essential for slowing kidney function advancement through behavior adjustments, such as physical exercise, dietary changes, patient monitoring (eg, blood pressure [BP] and blood glucose), and adherence to medication [ 9 ]. Patients with CKD may benefit from knowledge to change their behavior, improve their outcomes, and lower their mortality rates [ 10 ]. Considering the increasing prevalence of CKD, only 6% of the general population and 10% of those at high risk are aware of their CKD status in LMIC [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This low health literacy and unawareness in the early stage of the disease are ultimately responsible for CKD disease progression [ 12 ]. It has been noted, however, that proper CKD knowledge and management as well as mitigation of CKD-related risks may delay the progression to ESRD and other interrelated health consequences [ 10 , 13 ]. However, most of the patient education research regarding CKD has focused on patients with ESRD.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, self-care amongst patients with CKD was not associated with CKD stage, age, income status or education status. In contrast, Tsai YC et al 42 found that older patients had better self-care behaviour while younger ones had better disease knowledge. The same study reported self-care behaviour increased as renal function deteriorated.…”
Section: Discussionmentioning
confidence: 89%
“… 12 , 13 , 14 , 15 Similar to these individual-level observations, our findings reflect that the universal CKD care programs could decline the long-term trend of dialysis incidence. Although the fundamental mechanisms of the results are yet to be clarified, recent evidence suggests that more appropriate medication prescriptions, 5 , 16 education and dietary interventions, 17 , 18 complication management, 19 dialysis preparation, 20 as well as their interactions may play essential roles in prolonging kidney disease progression and dialysis initiation. In addition, our results, together with previous reports, 5 , 12 , 21 suggested that the care programs could significantly reduce cardiovascular disease or infectious disease-related mortality, particularly in the first year of dialysis, through improving the electrolyte imbalance correction and arteriovenous fistula preparation.…”
Section: Discussionmentioning
confidence: 99%